Mitochondrial quality control in cardiac microvascular ischemia-reperfusion injury: New insights into the mechanisms and therapeutic potentials. (June 2020) - Wang, Jin; Toan, Sam; Zhou, Hao
Graphical abstract: Abstract: Thrombolytic therapy and revascularization strategies create a complete recanalization of the occluded epicardial coronary artery in patients with myocardial infarction (MI). However, about 35 % of patients still experience an impaired myocardial reperfusion, which is termed a no-reflow phenomenon mainly caused by cardiac microvascular ischemia-reperfusion (I/R) injury. Mitochondria are essential for microvascular endothelial cells' survival, both because of their roles as metabolic energy producers and as regulators of programmed cell death. Mitochondrial structure and function are regulated by a mitochondrial quality control (MQC) system, a series of processes including mitochondrial biogenesis, mitochondrial dynamics/mitophagy, mitochondrial proteostasis, and mitochondria-mediated cell death. Our review discusses the MQC mechanisms and how they are linked to cardiac microvascular I/R injury. Additionally, we will summarize the molecular basis that results in defective MQC mechanisms and present potential therapeutic interventions for improving MQC in cardiac microvascular I/R injury.